The optimization of traffic signal timing for emergency evacuation using the simulated annealing algorithm - Jahangiri, Arash; Afandizadeh, Shahriar; Kalantari, Navid (Transport, 2011)
In recent years, natural and man-made disasters have increased and consequently put people's lives in danger more than before. Some of the crises are predictable. In these cases, there is a limited time for effective respond minimizing fatalities when people should be evacuated in a short time. Therefore, a transportation network plays a key role in evacuation. Hence, the outbound paths of urban networks are not sufficient from the viewpoint of number and capacity to encounter a huge amount of people; furthermore, it is costly to construct new routes or increase the capacity of the existing ones. Thus, a better utilization of the existing infrastructure should be considered. The article presents a model that determines optimum signal timing and increases the outbound capacity of the network. Moreover, in regard for the magnitude of the problem, an optimal solution could not be reached employing ordinary methods; therefore, the simulated annealing algorithm which is a meta-heuristic technique is used. The results of this study demonstrated that the objective function of the problem was greatly improved.First Published Online: 07 Jul 2011